Decorated Mould-Blown Glass Vessels from the Ancient City of Philadelpheia (Isauria – Cilicia Tracheia) - Hatice KÖRSULU; A. Sezai GEÇİT (Arkhaia Anatolika)
The ancient city of Philadelpheia, founded in the region of Isauria-Cilicia Trachea, is situated north of the modern village of Gökçeseki in the Ermenek district of Karaman province. In the necropolis of the ancient city, a salvage excavation was conducted in 2015. During the excavations, a large number of archaeological finds were discovered within an area of 10x10 m. The focus of this study is the decorated mould-blown glass vessels recovered from this area. These vessels include a flask with mythological figures, amphoriskoi/flasks, a lotus-bud beaker, a bottle decorated with lotus buds, a beaker with herringbone decoration, and a bottle with honeycomb pattern. Only a small part of the flask with mythological figures was preserved. It is a special vessel with scenes on both sides associated with Aias, a hero of the Trojan War. The amphoriskoi/flasks, with four specimens, are more numerous than the others. The types produced in two-part moulds have similar decorations of floral and geometric motifs. The lotus-bud beaker and the bottle with lotus buds both display the same characteristics in terms of colour and decoration. The stylized herringbone pattern on the beaker with herringbone decoration is rendered on the surface of the vessel, in a geometric style. The decoration resembling honeycomb is the characteristic feature of the bottle with the honeycomb pattern. A general dating, based on their technique, form, and decoration characteristics, would place the vessels between the 1st and 2nd centuries AD. Each of the decorated mould-blown specimens found in Philadelpheia is a vessel of special production. Since there is no evidence of glass production in the city, they must have been imported from the East. As the vessels were found in the necropolis of the city, they are considered to be associated with funerary ceremonies. The presence of these high-quality and likely expensive glass vessels reflects the wealth and prosperity of the city during the early Roman Imperial period.